Kajian Produksi Kopi Arabika (Coffea arabica) pada Berbagai Ketinggian Tempat di Kabupaten Temanggung - Fiqhry, Aqly Tyasna; Santoso, Tri Nugraha Budi; Ardiani, Fani (Jurnal Agro Industri Perkebunan, 2024)
Several factors, including the less-than-optimal altitude of Arabica coffee planting influence the low productivity of Arabica coffee in Temanggung Regency. The lack of rejuvenation of production plants means that old coffee plants have low productivity; apart from these two factors, farmers do not have good plant management skills. This research further examines the influence of altitude on Arabica coffee production. This research was carried out in Temanggung Regency, with the sub-districts that were the sample for this research being Ngadirejo District, with an altitude range of 900-1150 m asl, Parakan District, with an altitude range of 1150-1400 m asl, and Kledung District with an altitude range of more than 1400 m asl. The sampling method employed in this study is a purposive sampling technique; the researcher directly determines the location and source of research information. A total of 28 participants responded to this study, with an assessment sample taken of 5% of the population of Arabica coffee plantations that bear fruit. The analysis used the linear regression method of a fixed variable, namely height, and independent variables, namely production, productivity, and evaluation, with a significance level of 5%. The research results show that altitude does influence productivity. If altitude increases, productivity will also increase.